Special Paper 430: Plates, Plumes and Planetary Processes 2007
DOI: 10.1130/2007.2430(35)
|View full text |Cite
|
Sign up to set email alerts
|

K-T magmatism and basin tectonism in western Rajasthan, India, results from extensional tectonics and not from Réunion plume activity

Abstract: Evolution of sedimentary basins took place in the Barmer, Jaisalmer and Bikaner regions during K-T (Cretaceous-Tertiary) time in western Rajasthan, India. These intra-cratonic rift basins developed under an extensional tectonic regime from early Jurassic to Tertiary time. Rift evolution resulted in alkaline magmatism at the rift margins. This magmatism is dated at 68.5 Ma and has been considered to be an early phase of Deccan volcanism. Deccan volcanism, sedimentary basin development and the alkaline magmatism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…A mantle-plume origin for the Deccan Traps has been questioned, with many aspects of the Deccan geology inconsistent with that predicted by the plume-head model (Sheth, 2005a(Sheth, , 2005b(Sheth, , 2007, and we suggest that the two non-coaxial episodes of rifting observed within early deposits of the Barmer Basin are better explained by a model of plate reorganisations that initiated long before the arrival of the R eunion Mantle Plume (e.g. Sharma, 2007;Collier et al, 2008). This, combined with a lack of evidence for significant pre-Deccan regional unconformities, and only minor Deccan-age volcanism within the Barmer Basin (Basu et al, 1993;Sen et al, 2012), suggests that rifting did not occur above anomalously hot asthenosphere, despite the rift being situated within the inferred limits of the R eunion plume-head (Fig.…”
Section: Regional Context and Implicationsmentioning
confidence: 62%
See 3 more Smart Citations
“…A mantle-plume origin for the Deccan Traps has been questioned, with many aspects of the Deccan geology inconsistent with that predicted by the plume-head model (Sheth, 2005a(Sheth, , 2005b(Sheth, , 2007, and we suggest that the two non-coaxial episodes of rifting observed within early deposits of the Barmer Basin are better explained by a model of plate reorganisations that initiated long before the arrival of the R eunion Mantle Plume (e.g. Sharma, 2007;Collier et al, 2008). This, combined with a lack of evidence for significant pre-Deccan regional unconformities, and only minor Deccan-age volcanism within the Barmer Basin (Basu et al, 1993;Sen et al, 2012), suggests that rifting did not occur above anomalously hot asthenosphere, despite the rift being situated within the inferred limits of the R eunion plume-head (Fig.…”
Section: Regional Context and Implicationsmentioning
confidence: 62%
“…Evidence for post-volcanic uplift -not confined to the Deccan province -with antecedent drainage patterns, long-lived ( 8e9 Ma) eruptions (Sheth and Pande, 2014), pre-Deccan planation surfaces that suggest tectonic stability, a 10 R eunion Mantle Plume palaeolatitude disparity, and a lack of evidence for thinned, sub-Deccan lithosphere, are all inconsistent with the plume-head model (Sheth, 2005a(Sheth, , 2007. Seychelles rifting is also suggested to have resulted from plate reorganisations underway long before the arrival of the R eunion Mantle Plume (Sharma, 2007;Collier et al, 2008) and continued after the main Deccan eruptions (Armitage et al, 2011). Similarly, rather than being formed as part of the Reunion Mantle Plume 'tail,' the Mascarene Plateau (and possibly LakshadweepChagos Ridge) may be underpinned by thinned Proterozoic continental lithosphere that was situated between the Greater Indian and Madagascan continents prior to successful separation (Torsvik et al, 2013).…”
Section: Plate Tectonic Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Morgan, 1971;Plummer & Belle, 1995;Simonetti et al, 1995). However, alternative views suggest that Seychelles rifting resulted from external plate boundary forces (Sheth, 2005a;Sharma, 2007;Collier et al, 2008;Bladon et al, 2015), and many aspects of the Deccan geology have been shown to be inconsistent with plume activity, being more typical of deep-seated rifting (Sheth, 2005a(Sheth, ,b, 2007Sharma, 2007). In addition, the thick sequence of late Cretaceous to Eocene sediments (>6 km) in the Barmer Basin is counter to the impingement of a mantle plume beneath northwest India near to the Cretaceous-Paleogene boundary, despite the presence of multiple rift-related unconformities within the rift.…”
Section: Geological Backgroundmentioning
confidence: 99%